Back to business? Taking lessons from Porto (Portugal) to inform sustainable tourism futures after COVID-19 - Inês Gusman; José Alberto Rio Fernandes; Pedro Chamusca (Boletín de la Asociación de Geógrafos Españoles)
Porto has undergone significant economic and social changes in recent decades, closely intertwined with the evolution of its tourism sector. This research examines the vulnerabilities brought to light by the COVID-19 pandemic of this tourist city and tracks the resultant changes. We conducted an analysis of a set of variables focusing on the changes that have occurred during two distinct periods: during and post COVID-19. The data are analysed through longitudinal, comparative, and spatial approaches. The findings indicate the high exposure of Porto's tourism sector to international demand. Currently, the tourism sector growth exceeds 2019 levels and the challenges related to tourism development and its impact on local communities persist. Despite efforts to diversify tourism, the overall landscape seems largely unchanged from the pre-pandemic scenario. The vulnerabilities highlighted during the pandemic should guide the development towards a more sustainable future. It is crucial to maintain the multifunctionality of cities, particularly in the most tourist-driven areas, accommodating diverse activities alongside tourism, including residential, economic, and administrative functions.